Teaching Asian Geographies: Overcoming Pedagogical Barriers - EAA Editorial Office (Education About Asia, 2021)
Understanding geography, especially physical geography, is not easy for me. A deceased relative once described this ineptness as “not having even a bump of locality.” This handicap notwithstanding, my advocacy for geographic literacy in general, and geographic understanding of Asia in particular, as essential foundations of liberal and international education becomes stronger each year. Despite enormous digital advances in pedagogy, the apparent persistence of widespread geographic illiteracy demands effective, content-rich, and innovative instruction, as well as careful reflection, and high expectations of students. Hopefully, the following entries from the EAA archives assist readers interested in improving both student and one’s own levels of geographic literacy.
Keywords: Asia General; China; East Asia; Education; Geography; History; Japan; Pedagogy; Southeast Asia